(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The concept of development is distinct from social change, as it refers to an intentional process guided by specific policies and supervised by national and local bodies. Its aim is to introduce new systems and social forces, redirect existing forces, and create conditions for this type of change. Information technology plays a crucial role in the administrative, social, political, and economic development of society in the knowledge era. It permeates all aspects of our lives, from television to mobile phones and kitchen appliances. Luxury has become an everyday necessity. This research focuses on the importance of the knowledge economy and information technology training in Iraq’s transitioning economy. It aims to identify their role in achieving rapid development across all sectors and provide scientific findings and recommendations. The research emphasizes the significance of investing in economic knowledge, IT training, social organization, program nature, and employee activity within the development program. Ultimately, the research aims to present the key findings and recommendations to facilitate comprehensive development in various fields